Interpretation of Airborne Radiometric Data of a Typical Basement Complex, Northwest Nigeria - Ologe, O.; Moyi, A. M.; Sanusi, F.; Tsafe, U. H.; Umar, S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Interpretation of High resolution airborne radiometric data over Funtua-Tsafe Northwest Nigeria was carried out with the aim of delineating geological structures and mineral potential of the basement terrain. The data were interpreted quantitatively using the radiometric ratio and ternary radioelement signatures. Analysis of the radiometric data enabled the estimation of relative abundances of natural radioactive elements (Uranium, Thorium and Potassium) concentrations revealing distinct anomalies indicative of hydrothermal alteration and the structural styles (shear zones and fault systems) of the area. The count rate range of Uranium (2.0 to 7.6ppm), Thorium (10.6 to 40.0 ppm) and Potassium (0.5 to 3.1 %) were estimated within the area. High concentrations of the two radioelements (U,Th) are predominant in the western part of the area and are possible site for radiogenic heat exploration and geothermal alteration. From the qualitative analysis of the relative abundance of the radioactive elements and the ratio map analysis, rock bearing minerals such as pegmatite, schists were suggested to be present, which could serve as raw materials for many industries in Nigeria.